Multimodal imaging for tumour characterization from micro‐ to macroscopic level using a newly developed dorsal chamber designed for long‐term follow‐up. Issue 1 (23rd October 2019) - Rouffiac, Valérie; Ser‐Le Roux, Karine; Salomé‐Desnoulez, Sophie; Leguerney, Ingrid; Ginefri, Jean‐Christophe; Sébrié, Catherine; Jourdain, Laurène; Lécluse, Yann; Laplace‐Builhé, Corinne
Abstract: Optical imaging of living animals is a unique method of studying the dynamics of physiological and pathological processes at a subcellular level. One‐shot acquisitions at high resolution can be achieved on exteriorized organs before animal euthanasia. For longitudinal follow‐up, intravital imaging can be used and involves imaging windows implanted in cranial, thoracic or dorsal regions. Several imaging window models exist, but none have proven to be applicable for long‐term monitoring and most biological processes take place over several weeks. Moreover, none are compatible with multiple imaging modalities, meaning that different biological parameters cannot be assessed in an individual animal. We developed a new dorsal chamber that was well tolerated by mice (over several months) and allowed individual and collective cell tracking and behaviour analysis by optical imaging, ultrasound and magnetic resonance tomography. This new model broadens potential applications to areas requiring study of long‐term biological processes, as in cancer research. Abstract : Preclinical in vivo study of molecular and cell interactions dynamics can be achieved in photon imaging thanks to implantable chambers, allowing the multiscale observation from isolated cell to whole organ. We developed a new dorsal chamber very well tolerated by the mice model, making then possible dynamic and long‐term imaging without side effects. Designed for multimodality imaging, the tool is also compatible with sonography, X‐ray and magnetic resonance imaging for multiparametric characterization.